2021
DOI: 10.1007/s40271-021-00525-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives and Experiences of Preventive Treatments and Self-Injectable Devices for Migraine: A Focus Group Study

Abstract: Background Although several self-injectable preventive treatments for migraine have become available, they are not yet widely used. Thus, understanding patients' perceptions towards them is limited. Objective This study aimed to inform the design of a preference-elicitation instrument, which is being developed to quantify preventive treatment preferences of people with migraine. Methods We conducted a qualitative study involving nine in-person focus groups (three per country) in the United States, the United K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This study benefitted from a best-practice mixed methods design [56][57][58]. The attributes in the DCE were identified through a targeted literature review and nine in-person focus groups conducted in the US, UK, and Germany, during which patients simulated using unbranded auto-injectors and prefilled syringes [27]. The DCE was also qualitatively and quantitatively pilot-tested before surveying Japanese patients and physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study benefitted from a best-practice mixed methods design [56][57][58]. The attributes in the DCE were identified through a targeted literature review and nine in-person focus groups conducted in the US, UK, and Germany, during which patients simulated using unbranded auto-injectors and prefilled syringes [27]. The DCE was also qualitatively and quantitatively pilot-tested before surveying Japanese patients and physicians.…”
Section: Discussionmentioning
confidence: 99%
“…The DCE was also qualitatively and quantitatively pilot-tested before surveying Japanese patients and physicians. In addition, in order to address possible challenges in communicating auto-injector attribute levels to participants, the patient information leaflets for CGRP mAbs and the findings of the focus group study [ 27 ] were used to develop a short video to help participants to understand the attributes and to distinguish their levels. This was especially important for attributes describing different parts of the devices, such as the base and dose confirmation window, which would not be familiar to participants who have not used such devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Further, the focus group study conducted in 2019 in the US, UK, and Germany, in patients using or who had used preventive treatments for migraine showed that the top priority for patients was to reduce migraine attack severity and frequency. 34 Patients also reported dissatisfaction with oral preventive treatments due to intolerance or adverse events and were willing to self-inject efficacious and tolerable preventive treatments via syringes or autoinjectors. 34 However, most of the patients in the study group lacked access to efficacious preventive treatments for migraine.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Patients also reported dissatisfaction with oral preventive treatments due to intolerance or adverse events and were willing to self-inject efficacious and tolerable preventive treatments via syringes or autoinjectors. 34 However, most of the patients in the study group lacked access to efficacious preventive treatments for migraine. The AHS 2021 consensus statement suggests preventive treatments in patients severely affected due to migraine for two or more days in a month, with any level A/B drugs categories as first- and second-line treatment, followed by CGRP mAb as third line treatment.…”
Section: Discussionmentioning
confidence: 99%